Message
010-0138-001 MESSAGE FROM MR. BEN TILLETT. Mr. Tillett came in and enquired about a letter he had sent to Sir Walter about some Conference be was asked to attend. He said it was sent in to us about three weeks ago. I told him that when Sir Walter returned we would let him know about it. MT. 292/946/10/151